The Prevention of Incisional Hernia Formation Using a Delayed-Release Polymer of Basic Fibroblast Growth Factor - Derek A. DuBay; Xue Wang; M. Ann Kuhn; Martin C. Robson; Michael Franz (2004)
We sought to reduce the high incidence of abdominal wall incisional hernias using sustained release growth factor therapy.